MENARA AIR TRAFFIC CONTROL (ATC) TERBAIK PADA BANDAR UDARA DI KAWASAN EROPA - AFRIKA - Ricky P Ricardianto; Charles An (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2015)
In 2011, the writer had already presented the article about the growth of ATC (Air Traffic Control) in North America. To gain more knowledge about ATC, this article is presenting the best ATCs in Europe and Africa. The information presented here are focused on the heights of the ATC to support the broaden view of the airports area and the newest designed used to cope the era. The height taken as example here is 80 m to compare with ATC in Soekarno Hatta which is only 61 m.